Dealing with the threats inherent in unproctored Internet testing of cognitive ability: Results from a large-scale operational test program - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2011)
There is little information available about operational systems of unproctored Internet testing (UIT) of cognitive ability and how they deal with the threats inherent in UIT. This descriptive study provides a much-needed empirical examination of a large-scale operational UIT system of cognitive ability that implemented test design and verification testing for increasing test security and honest responding. Test security evaluations showed item exposure and test overlap rates were acceptable. Aberrant score evaluations revealed that negative score change (higher unproctored scores than proctored ones) was negligible. Implications for UIT research are discussed.